Pengaruh Kualitas Pelayanan Terhadap Kepuasan Mahasiswa Institut Bisnis dan Ekonomi Indonesia - Toni Yuliadi; Erna Listiana; Ramadania (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
Education is the most important thing in life so that every human being has the right to get it. Education is a continuous learning process in all social activities so that humans continue to exist and develop. Higher Education is one of the providers of learning facilities and services, therefore, Higher Education must be able to provide the best service for students. In this research was conducted to analyze the effect of service quality on student satisfaction Pontianak Institute of Business and Economics partially. Based on the results of the Coefficient of Determination Test (R²) the magnitude of the coefficient of determination or R square is 0.760. This means that the effect of the independence variable (service quality) on the dependency variable (student satisfaction) is 0.760 or 76%. This indicates that 76% of the variable student satisfaction (Y) of the Indonesian Institute of Business and Economics is influenced by Tangible (X1), Reliability (X2), Responsiveness (X3), Assurance (X4), and Empathy (X5) variables. The remaining 24% is influenced by other variables. Based on the large proportion of respondents who are more dominant showing "satisfaction" with the services of the Indonesian Institute of Business.